I Don't Think You Like Me Very Much: Child Minority Status and Disadvantage Predict Relationship Quality With Teachers. (September 2015) - Fitzpatrick, Caroline; Côté-Lussier, Carolyn; Pagani, Linda S.; Blair, Clancy
Even when accounting for past performance, academic achievement can be influenced by teacher expectations, which are lower for disadvantaged and visible ethnic minority children. We use a Quebec (Canada) population-based sample ( N = 1, 311) to examine whether ethnicity and teacher-perceived signs of disadvantage in kindergarten predict child reports of their relationship with teachers in fourth grade. Results suggest that visible minority children were 50% less likely and perceived disadvantaged children were 32% less likely to report having a positive relationship with their teacher. The findings are discussed in terms of directing efforts toward reducing teacher prejudice and improving child academic success.